O conhecimento tecnológico pedagógico de conteúdos (TPACK) na prática docente em ciências naturais: a projeção do TPACK dos formadores nas intenções de ensino dos professores em formação na UFPA-Belém - VILLA-GARCÍA, Leidy Yurani (Universidade Federal do Pará, 2023)
This thesis proposes to advance the knowledge about the development of the Technological Pedagogical Content Knowledge (TPACK) in the training of bachelors, identifying the influence of the TPACK of the teacher educators who guide the disciplines of the teaching practice, in the teaching intentions of the teachers in training. on this specific case, the study addresses three central aspects: (i) Identification of the theoretical-methodological contributions evidenced by the state of the art (national and international) on the TPACK built before year 2020, (ii) Identification and analysis of the theoretical-methodological contributions that are evidenced in the TPACK of the mentor professors in the Natural Sciences Bachelor's program at UFPA, and the (iii) identification and analysis of the theoretical-methodological contributions of the TPACK of the mentor professors that are evidenced in the teaching intentions of the professors in training in the UFPA Bachelor's degree. The research used a qualitative methodology with an interpretive approach, as an instrumental case study, with which it was possible: characterize theoretical-methodological contributions that support the elements of TPACK in teaching practice and the indicators for their identification; identify the theoretical-methodological contributions in the practice of the mentor teacher through the analysis of the decisions and actions of the teachers who guide the disciplines of teaching practice during planning and teaching; and, finally, the theoretical-methodological contributions in the teaching intentions of the future teachers were identified. With this, the analysis leads us to verify that there is a projection of the TPACK of the mentor teachers in the teaching intentions of the teachers in training. Thus, the research offers a point of view on the inclusion of reflection in the dynamics of teaching practice in a specific context, in order to enhance the construction of the TPACK and contribute to improve the processes in which we learn to teach science from the experience. Among the relevant results, we can identify the theoreticalmethodological contributions that expanded the conceptual framework of the TPACK and allow us to analyze the TPACK that is being built through teaching practice in the Bachelor's degree. These results can be used by teacher trainers in postgraduate, undergraduate and basic education programs, as well as in open programs and courses with the intention that teachers in training and in service can identify their TPACK and develop it.